2021
DOI: 10.3390/app112110087
|View full text |Cite
|
Sign up to set email alerts
|

THz Range Low-Noise SIS Receivers for Space and Ground-Based Radio Astronomy

Abstract: We report on research in the field of low-noise receiving systems in the sub-terahertz (THz) range, carried out in recent years, aimed at developing receivers with quantum sensitivity for implementation in space and ground-based radio telescopes. Superconductor-Insulator-Superconductor (SIS) mixers based on high-quality tunnel junctions are the key elements of the most sensitive sub-THz heterodyne receivers. Motivations and physical background for technology improvement and optimization, as well as fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It can be seen that the value of the Y-factor at the best point reaches 5 dB, which corresponds to a receiver noise temperature of 24 K. The noise temperature values were obtained without corrections for losses in the beam splitter and the cryostat window; they are only twice the value of hf/k B in the range from 240 to 265 GHz. The dependence of the DSB noise temperature of the SIS receiver on the local oscillator frequency was measured [18]; it was shown that the obtained values meet the technical requirements to the 211-275 GHz receiver for the Millimetron space radio-telescope.…”
Section: Development and Testing Of The 211-275 Ghz Receiver For Mill...mentioning
confidence: 80%
See 2 more Smart Citations
“…It can be seen that the value of the Y-factor at the best point reaches 5 dB, which corresponds to a receiver noise temperature of 24 K. The noise temperature values were obtained without corrections for losses in the beam splitter and the cryostat window; they are only twice the value of hf/k B in the range from 240 to 265 GHz. The dependence of the DSB noise temperature of the SIS receiver on the local oscillator frequency was measured [18]; it was shown that the obtained values meet the technical requirements to the 211-275 GHz receiver for the Millimetron space radio-telescope.…”
Section: Development and Testing Of The 211-275 Ghz Receiver For Mill...mentioning
confidence: 80%
“…To achieve a low noise temperature, it is necessary to compensate for the significant capacitance of the SIS junction (Cp ≃ 0.085 pF/μm 2 ); for this purpose, the topology of the mixing element was developed and its operation was modeled [18]. To match the impedance of the SIS junction at a high frequency with a waveguide impedance of about 400 Ohm, a planar structure was used, consisting of sections of coplanar and microstrip Nb/SiO2/Nb lines (Fig.…”
Section: Development and Testing Of The 211-275 Ghz Receiver For Mill...mentioning
confidence: 99%
See 1 more Smart Citation
“…To realize a quantum-limited performance of the SIS mixers at sub-THz frequencies, tunnel junctions with very high tunnel current density are required. To achieve proper matching between such junctions and the receiving antenna, submicron SIS junctions were implemented [28,[30][31][32][33]. SIS mixers have already been successfully used for both space missions and ground-based telescopes (TELIS, CHAMP) [7,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, SIS junctions with an area down to 0.5 µm 2 have been fabricated by conventional photolithography processes. To improve the performance and the yield of SIS mixers and to ensure equality of the SIS junctions in the twin mixer circuits [32,33], implementation of electron-beam lithography is highly desirable. This is especially important for the development of SIS array receivers and the further increase in the SIS operating frequency above 1 THz.…”
Section: Resultsmentioning
confidence: 99%